Dynamics of past forest cover changes and future scenarios with implications for soil degradation in Misiones rainforest, Argentina - Navarro, María Fabiana; Calamari, Noelia Cecilia; Mosciaro, Maria Jesus (Elsevier, 2023)
Misiones rainforest is one of the most threatened subtropical forests worldwide. Anthropogenic pressure by agriculture and forestry expansion continues transforming landscapes with negative consequences on ecosystem service provision, such as soil erosion control. Understanding how land use and land cover change (LUCC) management, policies, and social factors influenced in the past, allows decision-makers to anticipate potential effects on future land use and soil loss, contributing to the sustainable planning and management of productive activities. We developed three spatially explicit scenarios for Misiones province by 2030 using the Dinamica EGO modeling platform: 1) Business as Usual (BAU), 2) Low Deforestation (ALTlow), and 3) High Deforestation (ALThigh), based on different international and domestic socioeconomic contexts. We used land cover data from 2002 to 2015 as well as biophysical, social-infrastructure, political-administrative factors, and legal restrictions to estimate changes that may occur by 2030. We analyzed magnitude, intensity, and spatial pattern of future forest cover changes through transition rates and a cellular automata allocation model. Moreover, we used the Universal Soil Loss Equation (USLE) integrated into a Geographic Information System (GIS) to determine soil water erosion and soil loss tolerance in each scenario. Our results revealed that around 19% of the remaining native forest would be transformed into either agriculture or cultivated forest by 2030 for all scenarios. In addition, and contrary to that trend, the ALTlow scenario showed a recovery of 3% of native forest. Regarding soil erosion, our study indicated that the mean annual soil loss by 2030 would range from 12.03 to 19.15 t. ha−1.year−1 for ALTlow and ALThigh scenarios, respectively. Additionally, between 21% and 31% of Misiones province showed soil loss values higher than tolerance. Our work shows that a 10% decrease in the deforestation rate, compared to the current rate, would lead not only to a recovery of native forest cover, but also to a reduction in soil loss of about 4.5 Mt.yr−1 by 2030. This study demonstrates the suitability of the applied model to simulate future LUCC processes and provides inputs for decision-making involving natural resource management and the potential impacts of these decisions on ecosystem services. Finally, our results highlight the need for appropriate policies and regulations, especially, in terms of land use change restrictions in areas of high erosion risk.